Impact of chewing bags, e-cigarettes, and combustible cigarettes on arterial stiffness and small airway function in healthy students - Hauck, Annabelle Susann; Buchwald, Isabel; Watz, Henrik; Trinkmann, Frederik; Söling, Charlotte; Rabenstein, Andrea; Ruether, Tobias; Mortensen, Kai; Drömann, Daniel; Franzen, Klaas Frederik (Toxics, 2023)
Several substitute products are discussed as a healthier alternative to smoking, thereunder e-cigarettes and smokeless tobacco products, e.g., chewing bags, which are increasingly used in this context. We investigated the acute effects of chewing bags compared to combustible cigarettes and e-cigarettes with and without nicotine on small airways and arterial stiffness in a head-to-head design. This single-center, four-arm cross-overstudy included 20 healthy occasional smokers (25 ± 0.6 years). On four test days, participants consumed one product per day. Before, during, and after consumption, peripheral and central hemodynamic as well as arterial stiffness parameters were measured by Mobil-O-Graph™ (I.E.M., Germany). Resistance and small airway function were assessed by tremoFlo® c-100 (THORASYS Thoracic Medical Systems Inc.). The combustible cigarette and the e-cigarettes with and without nicotine significantly increased the resistance of the small airways (p < 0.05), while chewing bags had no effect. All nicotine containing products (e-cigarette with nicotine, combustible cigarette, chewing bag) as well as the e-cigarette without nicotine significantly increased parameters of hemodynamic and arterial stiffness. Changes in blood pressure and arterial stiffness were similar after smoking, vaping, and using chewing bags. We conclude that e-cigarettes and combustible cigarettes have similar acute harmful effects on small airway dysfunction. All nicotine containing products are associated with an increased cardiovascular risk compared with no product use.